Understanding the scope of internal organizational communication and teaching performance in educational institutions - Caballero Pacheco, Luis Benjamín (2019)
Organizational communication is a topic that has been little researched, as well as its relationship with teaching performance. In the pursuit of educational quality and the fulfillment of the institutional objectives by the directors of an educational institution, organizational communication gains strength as a pillar that relates not only to the performance of the teaching staff, but also to the organizational culture and the work climate. From Lexicology and Lexicography, it is important to know these terms and contrast them with what the DRAE proposes. The description of a group of terms associated with this field will allow to know a basic vocabulary that every researcher should know about this field. Methodologically, the data is ordered as follows: the entry is proposed, then the definition and, finally, the comments on the word studied. With this research, it is concluded that this kind of lexical studies can enrich other scientific disciplines. Likewise, it is crucial to understand the meanings of this kind of terms so that they are properly managed in educational and related management studies.